Mythos eaudiobook - Fry, Stephen (Mythos, 2019)
Mythos is a modern collection of Greek myths, stylishly retold by legendary writer, actor, and comedian Stephen Fry. Fry transforms the adventures of Zeus and the Olympians into emotionally resonant and deeply funny stories, without losing any of their original wonder. This stunning book features classical artwork inspired by the myths, as well as learned notes from the author. • Each adventure is infused with Fry's distinctive wit, voice, and writing style • Connoisseurs of the Greek myths will appreciate this fresh-yet-reverential interpretation, while newcomers will feel welcome • Retellings brim with humor and emotion and offer rich cultural context Celebrating the thrills, grandeur, and unabashed fun of the Greek myths, Mythos breathes life into ancient tales—from Pandora's box to Prometheus's fire. This audiobook invites you to explore a captivating world with the brilliant storyteller Stephen Fry as your guide.